Hospitalisation patterns of patients with interstitial lung disease in the light of comorbidities and medical treatment - a German claims data analysis - Wälscher, Julia; Witt, Sabine; Schwarzkopf, Larissa; Kreuter, Michael (Respiratory research, 2020)
Interstitial lung disease (ILD) is a heterogeneous group of mainly chronic lung diseases differing in disease course and prognosis. For most subtypes, evidence on relevance and outcomes of hospitalisations is lacking.